2011
DOI: 10.1117/12.892419
|View full text |Cite
|
Sign up to set email alerts
|

Quantum enhancement of a coherent ladar receiver using phase-sensitive amplification

Abstract: We demonstrate a balanced-homodyne LADAR receiver employing a phase-sensitive amplifier (PSA) to raise the effective photon detection efficiency (PDE) to nearly 100%. Since typical LADAR receivers suffer from losses in the receive optical train that routinely limit overall PDE to less than 50% thus degrading SNR, PSA can provide significant improvement through amplification with noise figure near 0 dB. Receiver inefficiencies arise from sub-unity quantum efficiency, array fill factors, signal-local oscillator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…For PSA, the gain during optical parametric amplification varies with the phase between the signal light and the pump light. It has been demonstrated that the PSA process does not introduce additional noise and therefore has the capability of noiseless amplification [20]- [23] .…”
Section: Noiseless Phase-sensitive Amplificationmentioning
confidence: 99%
“…For PSA, the gain during optical parametric amplification varies with the phase between the signal light and the pump light. It has been demonstrated that the PSA process does not introduce additional noise and therefore has the capability of noiseless amplification [20]- [23] .…”
Section: Noiseless Phase-sensitive Amplificationmentioning
confidence: 99%
“…In a quantum ladar system, the technology of phase-sensitive amplification [11] and squeezed-vacuum injection are developed to enhance to improve the resolution of ladar [12,13]. It is shown that a coherent ladar that employs phase-sensitive amplification prior to homodyne detection, owns a superior spatial resolution, including distance and angular.…”
Section: B Quantum Ladar and Quantum Illumination Radarmentioning
confidence: 99%
“…However, the values of τ in the Harris Corp. GCSD experiments [5] are ∼200 psec while the integration time in their system is T I ∼ 1 μsec, owing to the slow photodetectors employed. Therefore, the edge effects of pulses being cut off by the integration interval are negligible.…”
Section: Homodyne Photocount Operatormentioning
confidence: 99%
“…In the architecture conceived for the Harris experiments [5], the LO temporal waveform ξ T (t) is the same as the PSA pump waveform and the SVI pump waveform is advanced by the roundtrip time delay, 2Δ, between the detector and pupil planes. Similar to Subsec.…”
Section: Quantum-enhanced Ladar Systemmentioning
confidence: 99%